2014
DOI: 10.1007/s12149-014-0910-1
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and performance of lymphoscintigraphy in sentinel lymph node biopsy for early cervical cancer: results of the prospective multicenter SENTICOL study

Abstract: ObjectiveTo evaluate feasibility, SLN detection rate, and SLN location of lymphoscintigraphy in sentinel lymph node (SLN) biopsy for early cervical cancer.MethodsAncillary analysis of data from the multicenter prospective SENTICOL study (January 2005–June 2007) of patients with early cervical cancer (FIGO stage IA with emboli to IB1) was conducted. Preoperative lymphoscintigraphy was performed after intracervical administration of 60 or 120 MBq of 99mTc-labeled radiocolloid on the day before (long protocol) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…No SLN was found in the upper para-aortic region, and this was similar to that reported by Martínez et al 11 The detection of SLN in the presacral region was seen in 4 patients (3%), which was comparable to that reported in the SENTICOL study. 4 Despite detailed examination of the histological specimens, no involved nodes were identified in the parametrial region in 108 patients, unlike in the SENTICOL study. 4,13,27 The main challenge in identifying SLNs in this region is the very high signal originating from the primary cervical site because of its close proximity.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…No SLN was found in the upper para-aortic region, and this was similar to that reported by Martínez et al 11 The detection of SLN in the presacral region was seen in 4 patients (3%), which was comparable to that reported in the SENTICOL study. 4 Despite detailed examination of the histological specimens, no involved nodes were identified in the parametrial region in 108 patients, unlike in the SENTICOL study. 4,13,27 The main challenge in identifying SLNs in this region is the very high signal originating from the primary cervical site because of its close proximity.…”
Section: Discussionmentioning
confidence: 76%
“…Few studies have reported the SLN locations by different methods of detection (SPECT/CT scan, gamma probe, and blue dye). 4,11,12,27,28 These studies describe overall SLN locations in different regions of the pelvis, but not all commented on laterality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The feasibility of lymphoscintigraphy, and the factors associated with preoperative detection have been reported elsewhere [16].…”
Section: Preoperative Detection Of Sentinel Lymph Nodesmentioning
confidence: 99%